2014
DOI: 10.1007/s11434-014-0505-1
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-inferred Holocene vegetation and climate histories in Taro Co, southwestern Tibetan Plateau

Abstract: A 310-cm-long sediment core, covering the last 10,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 58 publications
2
34
1
Order By: Relevance
“…The lack of unconformities in the sediment texture and stable amounts of terrigenous elements such as Ti, Zr, and Hf (Figure , discussed later) prove the reliability of the age model. A previous study also suggested a nearly constant sedimentation rate in the Taro Co catchment during the whole Holocene [ Ma et al ., ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of unconformities in the sediment texture and stable amounts of terrigenous elements such as Ti, Zr, and Hf (Figure , discussed later) prove the reliability of the age model. A previous study also suggested a nearly constant sedimentation rate in the Taro Co catchment during the whole Holocene [ Ma et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Taro Co (31.05°–31.22°N, 83.92°–84.33°E, 4566 m above sea level, Figure a) is a freshwater lake with a surface area and catchment area of about 486.6 km 2 and 6924.4 km 2 , respectively [ Ma et al ., ; Guo et al ., ]. The lake had outflows during the Holocene, whereas it has been a closed lake system since 1200 cal years B.P.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herzschuh (2007) proposed that the A/Cy ratio could serve as a valuable tool for separating high-cold meadow from steppe vegetation in the central and northeastern TP. However, the A/ Cy ratio was used as an indicator of humidity rather than temperature at Lake Naleng Co in the eastern TP (Kramer et al 2010b) and at Lake Taro Co in the southwestern TP (Ma et al 2014). This ratio has also been used as a temperature indicator for palaeoclimate reconstructions at Lake Zigetang Co (Herzschuh et al 2006) and Lake Nam Co in the central TP.…”
Section: Pollen-climate Relationshipsmentioning
confidence: 99%
“…A modern pollen training set is crucial for a quantitative reconstruction. Some studies in the southern TP have revealed that steppe or meadow vegetation was present during the Holocene period Ma et al 2014;Miehe et al 2014). However, a large data set potentially increases noise as a result of increased ecological variability not captured in the fossil samples, which will lead to large errors in the reconstruction.…”
Section: Implications Of Modern Pollen Spectra For Palaeoenvironmentamentioning
confidence: 99%